2020
DOI: 10.1177/0954405420982222
|View full text |Cite
|
Sign up to set email alerts
|

Water-jet cavitation shocking as a novel array micro-forming technique

Abstract: Micro-feature arrays and large-area complex microscopic features on thin metallic sheet play an important role in micro-components. A novel technique-submerged water-jet cavitation shocking-is presented to generate micro-feature arrays on 304 stainless foils in this paper. High-speed camera shadowgraph images of the cavitation cloud were employed to analyze the impact zone. Then the forming depth, uniformity of forming depth and the thickness distribution of the micro-feature arrays were also studied. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, their proposed models are only reliable when the cavitation pit diameter-to-depth ratio is approximate to 1 which cannot adapt to various situations. Currently, our group 1517 reported a wide application in micro-forming, and a recorded thinning rate as high as 13.6% was obtained. Subsequently, it was found that the graded 2 titanium ultra-thin metallic sheets have complicated deformation and fracture behaviors in the process of water cavitation, which has not been taken seriously by other researchers.…”
Section: Introductionmentioning
confidence: 99%
“…However, their proposed models are only reliable when the cavitation pit diameter-to-depth ratio is approximate to 1 which cannot adapt to various situations. Currently, our group 1517 reported a wide application in micro-forming, and a recorded thinning rate as high as 13.6% was obtained. Subsequently, it was found that the graded 2 titanium ultra-thin metallic sheets have complicated deformation and fracture behaviors in the process of water cavitation, which has not been taken seriously by other researchers.…”
Section: Introductionmentioning
confidence: 99%